Bangladesh : Accounting and Auditing - World Bank (Washington, DC, 2013)
This report provides an assessment of accounting and auditing practices within the broader context of the Bangladesh institutional framework and capacity needed to ensure the quality of corporate financial reporting. The accounting and auditing practices in Bangladesh suffer from institutional weaknesses in regulation, compliance, and enforcement of standards and rules. The preparation of financial statements and conduct of audits, in many cases, are not consistent with internationally acceptable standards and practices. Better-qualified graduates generally do not join the accounting profession because it is not viewed as a stepping-stone to a rewarding and prestigious career. The out-of-date legal requirements, widespread noncompliance with accounting and auditing standards, ineffective enforcement mechanism, poor quality accounting education and training, and inadequate adherence to professional ethics have contributed to the weakness of the financial reporting regime. The policy recommendations provided in this report focus on improving statutory framework, strengthening enforcement mechanisms, upgrading professional education and training, and enhancing capacity of regulatory and professional bodies. A major recommendation is that an independent oversight body-Financial Reporting Council-should be established. The Financial Reporting Council will be responsible for adopting, monitoring, and enforcing international accounting and auditing standards for financial reporting by the public-interest entities. In addition, arrangements will need to be made to develop a simplified financial reporting framework for small- and medium-size enterprises.